Corpos sagrados e desejos profanos: luxúria e ambiguidade em poemas de Decadência (1923), de Judith Teixeira - Oliveira, Larissa Bistafa Antunes de (Universidade Federal de São Carlos, 2026)
Judith Teixeira (1880–1959) was a Portuguese modernist poet whose work challenged the moral and aesthetic paradigms of her time, for which she faced severe recriminations. Due to the reception of her work at the time, Judith remained marginalized from the Portuguese literary canon for a long time. Her poems express the free and pluralistic nature of female desires, ranging from heterosexual eroticism to lesbian eroticism, configuring what the author herself called the force of “lust”. By assuming a subversive female voice conscious of her desiring power, Judith Teixeira occupies an aesthetic in-between space: she dialogues with the themes of Decadentism, with the experimentation and chronology of Modernism, and anticipates debates on gender and sexuality that would be taken up again by postmodern thought. Therefore, the present analysis aims to examine the construction of lust in Decadência (1923), considering its ambiguities, duplicities, and poetic transgressions. The theoretical contribution mainly draws on Georges Bataille's Erotism (1988), in addition to from feminist criticism and cultural studies, especially authors such as Showalter (1994), Klobucka (2009), Hélène Cixous (2022), Richard Rorty (2007) and Bhabha (2013), to discuss eroticism, subjectivity, and female discourse as forms of resistance. Thus, it is understood that Judith Teixeira inaugurates a poetics of transgression that transcends the limits of her time, reaffirming the power of writing as a space of desire, emancipation, and affirmation of the feminine.
Sacred bodies and profane desires: lust and ambiguity in Poems from Decadência (1923) by Judith Teixeira
Keywords: Luxúria; Modernista; Judith Teixeira; Erotismo; Escrita feminina/feminista; Poesia portuguesa; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA; 5. Igualdade de Gênero